Visions of Cardiomyocyte Fundamental Concepts of Heart Life and Disease - Tsipis, Angelos (IntechOpen, 2020)
In the field of cardiology, some of the most dramatic advances in recent years have come from understanding the molecular and cellular basis of cardiovascular disease. Knowledge of the pathological basis of disease in some cases allows the development of new strategies for prevention and treatment. This book was planned not only to convey new facts on cardiovascular diseases, but also to boost the excitement and challenges of research in the dynamic area of modern molecular and cellular biology of cardiology. The integration of multilevel biological data and the connection with clinical practice reveal the potential of personalized medicine, with future implications for prognosis, diagnosis, and management of cardiovascular diseases.